2002
DOI: 10.1086/324301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ions in L1544. I. Kinematics

Abstract: We have mapped the dense dark core L1544 in H13CO`(1È0), DCO`(2È1), DCO`(3È2), N 2 H( 1È0), (3È2), (2È1), (3È2), C18O (1È0), and C17O (1È0) using the IRAM 30 m tele-N 2 H`N 2 D`N 2 Ds cope. We have obtained supplementary observations of HC18O`(1È0), HC17O`(1È0), and D13CO( 2È1). Many of the observed maps show a general correlation with the distribution of dust continuum emission, in contrast to C18O (1È0) and C17O (1È0), which give clear evidence for depletion of CO at positions close to the continuum peak. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
237
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 197 publications
(273 citation statements)
references
References 29 publications
34
237
2
Order By: Relevance
“…N/10 12 cm −2 at a slightly bluer velocity compared to the ones of the parent species, which in turn are consistent with the systemic velocity of L1544 (7.2 km s −1 , Caselli et al 2002a). The difference, ca.…”
Section: Singly Deuterated Methanol (Ch 2 Doh)supporting
confidence: 80%
“…N/10 12 cm −2 at a slightly bluer velocity compared to the ones of the parent species, which in turn are consistent with the systemic velocity of L1544 (7.2 km s −1 , Caselli et al 2002a). The difference, ca.…”
Section: Singly Deuterated Methanol (Ch 2 Doh)supporting
confidence: 80%
“…3 is that in L1521F there is evidence for an "infall signature" although less marked than in L1544, where it is attributed to extended infall onto the core (Williams et al 1999) or to central infall in a depleted core nucleus (Caselli et al 2002a). In fact, we see evidence for Table 2.…”
Section: Integrated Intensity Maps and Continuum Emissionmentioning
confidence: 98%
“…6.472 ± 0.001 0.299 ± 0.001 17.9 ± 0.1 5.859 ± 0.016 4.94 ± 0.03 N 2 H + (3−2) 6.388 ± 0.010 a 0.290 ± 0.030 1.4 ± 1.0 0.692 ± 0.075 5.1 ± 3.7 N 2 D + (2−1) 6.505 ± 0.004 0.268 ± 0.010 2.2 ± 0.4 0.978 ± 0.026 4.6 ± 0.9 N 2 D + (3−2) 6.507 ± 0.006 0.222 ± 0.024 1.2 ± 0.9 0.332 ± 0.029 4.1 ± 3.2 NOTE: a The N 2 H + (3−2) frequency is as in Caselli et al (2002a), whereas for the other lines we used the updated values determined by Dore et al (2004). b The integration includes all hyperfines.…”
Section: Integrated Intensity Maps and Continuum Emissionmentioning
confidence: 99%
“…Thus, the N 2 D + /N 2 H + abundance ratio and the N 2 D + fractional abundance increase towards the core center, so that N 2 D + is particularly suitable to investigate the kinematics as well as the physical and chemical conditions of the highly CO-depleted core nuclei. In fact, N 2 D + observations have recently allowed an accurate analysis of the velocity field and kinematics across the core nucleus of L1544, a well-known starless core (Caselli et al 2002a). N 2 D + lines can be used to determine the line of sight component of the velocity of ions in the densest portions of cloud cores.…”
Section: Introductionmentioning
confidence: 99%
“…As far as higher J transitions are concerned, Sastry et al (1981) observed unresolved rotational lines up to the J = 6 ← 5 one in the positive column of a DC glow discharge, while some hyperfine structure for the J = 2 → 1 and 3 → 2 transitions has been detected by several radioastronomers (Gerin et al 2001;Turner 2001;Caselli et al 2002a).…”
Section: Introductionmentioning
confidence: 99%